PELATIHAN PENULISAN KARYA ILMIAH BERBANTUAN AI (CHATGPT OPEN AI & MENDELEY REFERENCE MANAGER) UNTUK MAHASISWA PGSD - Serani, Gabriel; Parida, Lusila; Warkintin, Warkintin (JPPM: Jurnal Pelayanan dan Pemberdayaan Masyarakat, 2025)
Writing scientific papers is still a problem for students. Many lecturers complain about the systematic thinking, the sequence of ideas, the clarity of the presentation of theoretical aspects and the depth of analysis of problems or research results of students. Similar difficulties were also found in observations and experiences of guiding PGSD students of STKIP Persada Khatulistiwa Sintang. Therefore, this activity helps students overcome these difficulties by providing assistance in writing scientific papers with the help of one of the artificial intelligence technology products, namely Chat Generative Pre-trained Transforme (ChatGPT). ChatGPT is an intelligence-based machine technology developed by OpenAI, an artificial intelligence research laboratory based in Ohio, United States. ChatGPT is designed to be able to imitate human conversation using NLP (Natural Language Processing) technology. ChatGPT has the ability to produce structured and coherent writing. Apart from the controversy over its use in the world of education, the presence of ChatGPT technology is an opportunity that can be utilized to develop students' academic abilities. Assistance to recognize and use ChatGPT Open AI wisely is expected to foster students' interest and writing skills. Of course, students are equipped with insights and scientific writing techniques so that they can use this new technology in a scientific corridor by paying attention to originality and references that can be proven scientifically.